Evaluation of dental practitioner habits with occlusal assessment and the clinical application of practical techniques in occlusion, amongst a cohort of participants based in the UK, South Africa, Malta and Malaysia. (27th July 2022) - Mehta, Shamir B.; Rizzo, Daphne; Paulose, Bryan; Botbol, Alisa; Vijay, Sadhvik; Arjuna, Amar; Banerji, Subir
Abstract: Background: Currently, there is a lack of data relating to dental practitioners' habits with clinical occlusal assessment and the application of practical techniques in occlusion. Objectives: The aim of this study was to investigate habits with clinical occlusal assessment and the practical application of established concepts in occlusion amongst a cohort of international dentists. Methods: A piloted questionnaire with 20 statements was distributed by 5 recruiters. The recruiters were based in Malta (1), South Africa (1), Malaysia (1) and the UK (2). Outcomes were analysed using descriptives, chi‐squared and Fisher's exact test. All the analyses were carried out in Stata, Version 12. Significance was inferred at p < .05. Results: Four hundred thirty‐five completed responses were included in the sample (response rate, 70.7%). Overall, high levels of agreement were reported with the provision of single‐unit crown and onlay restorations (78.8%) and bridge prostheses (up to 3 units, 77.9%), respectively. One‐third (33.6%) agreed to observing dynamic occlusal relationships during an adult patient dental examination, 40.7% reported using articulators for crown and bridge cases, and 25.1% agreed to taking facebow records. Under half (47.3%) of the dentists expressed dissatisfaction with their undergraduate training in occlusion, with no significant association with the variables of the number of years of experience, the country of practice or being in general practice ( p ≥ .226). Conclusion: The results indicate a disparity between traditionally taught and applied concepts in clinical occlusion and the undertaking of occlusal assessments and the management of occlusion in clinical practice. Abstract : An evaluation of dental practitioner habits with occlusal assessment and the clinical application of practical techniques in occlusion, amongst a cohort of participants based in the UK, South Africa, Malta and Malaysia.